La revisión del artículo 145 CE en el contexto de una reforma federal de la Constitución - González García, Ignacio (Revista de Derecho Político, 2018)
Resumen: En el actual contexto de profunda crisis del modelo territorial diseñado por la Constitución Española de 1978, son muchos los autores que han abogado por una reforma del Estado de las Autonomías en clave federal. Bien para transformarlo plenamente en un Estado federal, bien para corregir en un sentido más federal algunos de sus instrumentos disfuncionales. Uno de ellos es, sin duda, la colaboración entre Comunidades Autónomas y, en particular, los convenios de cooperación interautonómicos. La doctrina ha venido manifestando que el muy escaso número de convenios celebrados entre Comunidades Autónomas trae causa de la rigidez de su régimen jurídico, recogido en el artículo 145 CE y en los correspondientes Estatutos de Autonomía. En consecuencia, se ha venido proponiendo, de manera mayoritaria y reiterada, la reforma del citado artículo 145 CE en la dirección de eliminar el control que las Cortes Generales ejercen sobre la celebración de estos pactos interautonómicos, en el entendido de que, además, así se le daría a este precepto constitucional una configuración más cercana a la que tendría en un verdadero Estado federal. En este trabajo se intenta justificar, sin embargo, que el régimen jurídico del artículo 145 CE no es la causa del deficiente funcionamiento de la colaboración horizontal en nuestro sistema, que el alcance de la potestad de control de las Cortes sobre estos convenios es muy distinto al descrito por la doctrina y que, además, la formulación actual del artículo 145 CE es plenamente compatible con la reconsideración en clave federal del resto del modelo territorial. Por todo ello, se defiende finalmente la improcedencia de la reforma constitucional propuesta. Summary I. The failure of our model of territorial power distribution and the discussion on its alternatives. II. The federal «solution»: its political and technical legal dimension. 2.1. The federalism as an exit to the crisis of the model. 2.2. The technical aspects of an eventual federal or federalizing reform. III. Federal amendment of Article 145 of Spanish Constitution: the scholar diagnosis to the problem and the proposals of review. IV. Diagnostic errors and unsuitability of the proposed reform. 4.1. The «rigidity» of Article 145 of Spanish Constitution neither is a cause nor a concurring cause. 4.2. The federal nature of this constitutional provision. 4.3. The real extent of Article 145 of Spanish Constitution and the authorizing control of the Cortes Generales. 4.4. The intervention of the parliament of the State as an act reviewable by the Constitutional Court. V. Concluding remarks. VI. References. Abstract: In the current context of serious crisis of the territorial pattern envisaged by the 1978 Spanish Constitution, many authors have advocated for a reform of the State of the Autonomies in federal terms, either for transforming it fully into a Federal State, or for correcting some of its most dysfunctional instruments towards a more federal orientation. One of them is certainly the cooperation between Autonomous Communities and, in particular, agreements on inter-autonomic cooperation. The scholars have pointed out that the cause of the low number of agreements between Autonomous Communities is the rigidity of their legal regime, contained in Article 145 of the Spanish Constitution and the corresponding Statutes of Autonomy. Consequently, it has been repeatedly and mostly proposed to amend the mentioned Article 145 in the sense of removing the control of the Cortes Generales over the establishment of these autonomic agreements, on the understanding that, moreover, this constitutional provision would receive a configuration closer to a real federal state. Notwithstanding, this paper attempts to justify that the legal regime of Article 145 of the Spanish Constitution is not the cause of the insufficient functioning of the horizontal cooperation in our system; that the scope of the powers of control of the Cortes on these agreements is very different to the described one by the authors; and, moreover, that the current wording of Article 145 is fully compatible with the review in federal terms of the rest of the territorial pattern. Thus, it is finally defended the unsuitability of the proposed constitutional reform.